Improving Creativity and Mathematics Learning Outcomes: Implementation of the Discovery Learning Model in Spatial Building Materials - Fitriyah Fitriyah (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
Creativity of thinking in learning Mathematics is the most important goal in improving learning outcomes, it has an important role in providing stimulation, enthusiasm and pleasure in learning so that those who have high motivation are the problem in research to improve creative thinking skills and math learning outcomes. The role of the math teacher in using the Discovery Learning model shows the importance of the real context according to the situation in the environment by the students themselves in thinking about identifying problems in learning so that the concepts received by students are more meaningful. Quantitative experimental research with research subjects of class VIII students of MTs Wahid Hasyim, school year 2023/2024. The data in this study are quantitative data obtained from tests of students' knowledge and understanding through questionnaire tests. The results of this study indicate: the effect of the Discovery Learning model in the mathematics subject of building space material to improve students' creative thinking by 70.2%, the effect of the Discovery Learning model in the mathematics subject of building space material to improve student learning outcomes by 86.3%, and the effect of the Discovery Learning model in the mathematics subject of building space material to improve creative thinking and learning outcomes together by 76.6%. This means that the application of the Discovery Learning model in improving creative thinking and student learning outcomes has a significant effect.